The macroeconomic effects of migrants' remittances in Moldova: a stock–flow consistent model - Edwin Le Heron; Nicolas Yol (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2019)
Migrants' remittances are an essential source of income in many developing countries. In this article, we build a post-Keynesian stock–flow consistent model adapted to Moldova, one of the top recipients of remittances. In addition to increasing household consumption, migrants' transfers have strong effects on economic growth in Moldova. However, remittances are very sensitive to the economic conditions in migrants' destination countries, especially since the 2008 global financial crisis. After including remittances in consumption behavior and lenders' risk, we run simulations to show how shocks in migrants' destination countries (that is, Europe and Russia) impact the Moldovan economy through fluctuations in remittances. First, the increasing instability of remittances explains a significant portion of the economic volatility experienced by Moldova. Second, the high level of imports implies a weak multiplier effect of remittances, leading to an unsustainable pattern of growth.
Keywords: E12; E32; F22; F24; F43; 330; remittances; Moldova; stock-flow consistent models; business cycles; migration; volatility